Synthesis and antibacterial evaluation of some novel mannich bases of benzimidazole derivatives - A. Ahmadi (Bulletin of the Chemical Society of Ethiopia, 2017)
Substituted benzimidazoles are known for their chemotherapeutic importance and many pharmacological properties. In this paper, we synthesized some novel Mannich bases of benzimidazole derivatives. The synthesized compounds were characterized by their physical and spectral data and in vitro antibacterial activity of these compounds tested against Bacillus subtilis, Bacillus pumilus, Escherichia coli and Pseudomonas aeruginosa organisms. The potency of the synthesized compounds was determined against standard drug Ciprofloxacin by measuring the zone of inhibition.